2022
DOI: 10.3389/fimmu.2022.855006
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of Long-Term Cognitive Impairment After Sepsis

Abstract: Sepsis is recognized as a life-threatening multi-organ dysfunction resulting from a dysregulated host response to infection. Although the incidence and mortality of sepsis decrease significantly due to timely implementation of anti-infective and support therapies, accumulating evidence suggests that a great proportion of survivors suffer from long-term cognitive impairment after hospital discharge, leading to decreased life quality and substantial caregiving burdens for family members. Several mechanisms have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 139 publications
0
16
0
Order By: Relevance
“…A recent systematic review found that cognitive impairment of sepsis survivors ranged from 12.5 to 21% [11]. Pathophysiological changes, such as blood-brain barrier dysregulation, neuroinflammation, neurotransmitter dysfunction, and neuronal loss are thought to be responsible for long-term cognitive impairments [21]. More recently, chronic conditions of sepsis-associated encephalopathy have been recognized, including memory impairment, attention deficit, language impairment, and executive dysfunction, which are present in more than half of sepsis survivors at the time of hospital discharge [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review found that cognitive impairment of sepsis survivors ranged from 12.5 to 21% [11]. Pathophysiological changes, such as blood-brain barrier dysregulation, neuroinflammation, neurotransmitter dysfunction, and neuronal loss are thought to be responsible for long-term cognitive impairments [21]. More recently, chronic conditions of sepsis-associated encephalopathy have been recognized, including memory impairment, attention deficit, language impairment, and executive dysfunction, which are present in more than half of sepsis survivors at the time of hospital discharge [22].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found that cognitive impairment of sepsis survivors ranged from 12.5 to 21% [11]. Pathophysiological changes, such as blood-brain barrier dysregulation, neuroinflammation, neurotransmitter dysfunction, and neuronal loss are thought to be responsible for long-term cognitive impairments [21].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the vast majority of research has intentionally excluded individuals with previous neurological and psychiatric disorders, who would have confounded the interpretation of the results [ 93 ]. Almost all studies reported the presence of a general cognitive decline [ 60 , 61 , 62 , 63 , 64 , 68 , 69 , 70 , 73 , 77 , 78 , 82 , 83 , 84 , 85 ] (see Table 2 ), which is a common sequela of other viral diseases, such as AIDS [ 112 , 113 ] and sepsis ([ 114 , 115 ]. In the literature, this status is often referred to as ‘Long COVID’ [ 116 , 117 ], or ‘brain fog’ with accompanied clinical symptoms, such as low energy, insomnia, problems in concentration and spatial orientation and difficulty in finding the right words [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral LPS-injection animal model has been shown to induce neuroinflammation and long-term cognitive deficits and has been widely used to investigate the pathogenesis of SAE and to test potential therapeutics [7,28,29]. To investigate the effects of LPS injection on survival rate, the mice were monitored for 7 days.…”
Section: Dexpramipexole Attenuates Lipopolysaccharide-induced Long-te...mentioning
confidence: 99%
“…SAE is associated with elevated mortality and morbidity and can cause long-term cognitive impairment in sepsis survivors, manifested mainly in declarative memory, working memory, processing speed and executive function [1][2][3]. To date, several animal models, including those based on lipopolysaccharide (LPS) injection and cecal ligation puncture, have been widely used to mimic clinical human sepsis in preclinical studies [4][5][6][7]. However, the precise pathological mechanisms underlying long-term cognitive impairment after sepsis remain largely unknown, and effective treatments are lacking [8].…”
Section: Introductionmentioning
confidence: 99%